Neosporosis en alpacas de la provincia de Huaytará, Huancavelica, Perú - Sante, Rubens (2018)
The aim of this study was to determine the seroprevalence of N. caninum antibodies, using the immunofluorescence antibody technique (IFAT), using a cut-off point of 1:100 in 288 alpacas from several populations in the province of Huaytará, Huancavelica, during 2016 and 2017. Blood samples plus situational and epidemiological information were collected. The seroprevalence was 16.3 ± 4.3% (47/288), without significant differences due to origin, age group and parity. The results show the presence of specific antibodies against N. caninum in the region.